Molecular aspects of β, β-carotene-9′, 10′-oxygenase 2 in carotenoid metabolism and diseases - Wu, Lei; Guo, Xin; Wang, Weiqun; Medeiros, Denis M.; Clarke, Stephen L.; Lucas, Edralin A.; Smith, Brenda J.; Lin, Dingbo (My University, 2016)
Carotenoids, the carotenes and xanthophylls, are essential components in human nutrition. β, β-carotene-9′, 10′-oxygenase 2 (BCO2), also named as β, β-carotene-9′, 10'-dioxygenase 2 (BCDO2) catalyzes the asymmetrical cleavage of carotenoids, whereas β, β-carotene-15, 15′-monooxygenase (BCMO1) conducts the symmetrical cleavage of pro-vitamin A carotenoids into retinoid. Unlike BCMO1, BCO2 has a broader substrate specificity and has been considered an alternative way to produce vitamin A. In contrast to BCMO1, a cytoplasmic protein, BCO2 is located in the inner mitochondrial membrane. The difference in cellular compartmentalization may reflect the different substrate specificity and physiological functions with respect to BCMO1 and BCO2. The BCO2 gene mutations are proven to be associated with yellow color of skin and fat tissue and milk in livestock. Mutation in intron 2 of BCO2 gene is also supposed to be related to the expression of IL-18, a pro-inflammatory cytokine associated with obesity, cardiovascular diseases, and type 2 diabetes. Further, BCO2 is associated with the development of mitochondrial oxidative stress, macular degeneration, anemia, and hepatic steatosis. This review of the literature will mostly address recent updates regarding the role of BCO2 in carotenoid metabolism, and discuss the potential impacts of BCO2 protein and the mutations in mammalian diseases.
Citation: Wu, L., Guo, X., Wang, W., Medeiros, D. M., Clarke, S. L., Lucas, E. A., … Lin, D. (2016). Molecular aspects of β, β-carotene-9′, 10′-oxygenase 2 in carotenoid metabolism and diseases. Experimental Biology and Medicine, 241(17), 1879–1887. https://doi.org/10.1177/1535370216657900
Keywords: β; β-carotene-9′; 10′-oxygenase 2; Carotenoid; Hepatic Steatosis; Interleukin 18